Wohlverhaltenspflichten nach § 63 Abs. 4, Abs. 5 WpHG (Product Governance) - Bartlitz, David (iff Infobrief)

L'évolution de la visibilité des musulmans de France dans l'espace public et numérique - Karaca, Resul (L'islam dans la culture populaire: reconfigurations et nouvelles visibilités)

Beethovens Eigenbearbeitungen und digitale Heuristik. Erkundungen mit den synoptischen Doppeleditionen und Analysewerkzeugen des Projekts Beethovens Werkstatt - Münzmay, Andreas

Gestärkt durchs Studium - Universitäre Unterstützungsangebote zum Stress- und Selbstmanagement - Bobe, Julia; Decker, Claudia; Klingsieck, Katrin B.

Zu Heidegger - Kommunikationsanalytische Studien - Markewitz, Friedrich
Martin Heideggers Einfluss reicht bis heute weit über enge disziplinäre Grenzen hinaus in die verschiedenen Geistes- und Kulturwissenschaften sowie die gesamtgesellschaftliche Öffentlichkeit hinein. Gleichzeitig werden er und seine Philosophie, insbesondere seit der Veröffentlichung seiner Denktagebücher, der ‚Schwarzen Hefte‘, aufgrund nationalsozialistischer Verstrickungen und antisemitischer Konnotationen kontrovers diskutiert. Trotz seiner diskursiven Herausgehobenheit und Relevanz stehen linguistische Aufarbeitungen zu Heideggers Kommunikationsverhalten bis heute weitestgehend aus. Die vorliegende kommunikationsanalytische Studie versteht sich als erster umfassender Versuch, Heideggers Kommunikationsverhalten in den Blick zu nehmen, um Charakteristika wie Problematiken des Heideggerischen Sprachgebrauchs aufzuarbeiten sowie zu reflektieren.
Keywords: Linguistische Hermeneutik; Kommunikationsanalyse; Invektivitätsforschung; Begriffsarbeit

The Economics of Ideologies - Gries, Thomas; Burs, Carina; Müller, Veronika
Many of the major international and intrastate crises and conflicts, but also the threat to democratic principles, are driven by belief systems and ideologies. They fuel political polarization, which is particularly evident in the battleground of social media. Nevertheless, we hardly pay attention to ideologies, their narratives, functions and organizations in economic theory today. Ideologies as “non-rational beliefs” seem incompatible with rationality in economic models. Therefore, the book examines the role of ideologies and belief systems in individual decision-making behavior from an economic and rational perspective. Due to the fact that people have incomplete information, belief systems and ideologies fulfill a number of important functions. While ideologies themselves serve psychological needs, they are used as a cognitive framework for rational decision-making once they have been adopted through a Bayesian learning process. They influence decisions in a wide range of areas, from consumption and work to politics. This is where the role of ideological organizations becomes important, because they determine the ideological direction of the narratives and their dissemination. Thus, ideologies give a normative direction, for better or for worse. The “quality” of ideological leadership can be evaluated normatively on the basis of principles such as individual sovereignty and human dignity. A democratic discourse requires an information and communication system that enables an evaluation of precisely these ideologies, free from resource and information power.

Automation 2035 - Gräßler, Iris; Özcan, Deniz; Tusek, Alena Marie; Bilgic, Attila; Lange, Christian; Stich, Christian; Maul, Christine; Heizmann, Michael; Weyrich, Michael; Dessel,, Sascha; Miny, Torben; Jumar, Ulrich
Executive summary Die vorliegende Zukunftsstudie „Automation 2035“ gibt einen Ausblick auf die Entwicklung der Automatisierungstechnik in den nächsten 10 Jahren. Neben der Beschreibung von Trends wie Kreislaufwirtschaft, Automatisierung der Märkte, Biologisierung, autonome Systeme und Robotik sowie IT-Sicherheit wird die zu erwartende Veränderung in der Bildung beschrieben. Dazu verwenden wir Methoden der Zukunftsforschung und arbeiten mit der Szenarientechnik, um Zukunftsperspektiven der Automation aufzuzeigen. Personas werden eingesetzt, um die zukünftigen Entwicklungen plastisch aus den Augen der Personen im Jahr 2025 und in der Zukunft im Jahr 2035 zu beschreiben. Schlüsselthemen und Trends: ... ... Inhalt Executive summary 1 1 Einführung 3 2 Zukunftsfelder für die Automatisierungstechnik 2035 4 2.1 Kreislaufwirtschaft 4 2.2 Automatisierung der Märkte 7 2.3 Biologisierung 8 2.4 Autonome Systeme und Robotik 10 2.5 Security 12 2.6 Veränderung der Ausbildung 13 3 Szenario der Automation 2035 16 4 Personas 18 4.1 Unternehmer 18 4.2 Ingenieurin 19 4.3 Schüler 20 5 Thesen und Ausblick 22 Methodik 24 Autorenteam 25 Schrifttum 26...

Reliabilität - Rumlich, Dominik (Leistungsmessung, Evaluation und Feedback im Fremdsprachenunterricht)

L'islam dans la culture populaire: Reconfigurations et nouvelles visiblités
La France contemporaine révèle un large éventail d’expressions d’une conscience(franco-)musulmane plurielle et visible. Cet ouvrage se penche sur ces nouvelles visibilités de l’islam dans la culture populaire et accorde une importance particulière au protagonisme des femmes musulmanes ainsi qu’à la culture populaire dans l’espace numérique. Il démontre également que la quête d’une nouvelle visibilité est à la fois un moteur d’intégration et de productivité culturelle, mais aussi génératrice de conflits.

Crime Fever. Colonial Pathologies in Émile Zola’s Thérèse Raquin (1867) - Schlieper, Hendrik (Bodies, Remedies, Policies. From Early Modern Chronicles of the Indies to Covid-19 Narratives)

Technikrecht - Ensthaler, Jürgen; Gesmann-Nuissl, Dagmar; Müller, Stefan

Benchmarking Knowledge Editing using Logical Rules - Moteu Ngoli, Tatiana; Kouagou, N'Dah Jean; Zahera, Hamada Mohamed Abdelsamee; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Semantic Web Conference (ISWC 2025))
Large Language Models (LLMs) are increasingly deployed in real-world applications that require access to up-to-date knowledge. However, retraining LLMs is computationally expensive. Therefore, knowledge editing techniques are crucial for maintaining current information and correcting erroneous assertions within pre-trained models. Current benchmarks for knowledge editing primarily focus on recalling edited facts, often neglecting their logical consequences. To address this limitation, we introduce a new benchmark designed to evaluate how knowledge editing methods handle the logical consequences of a single fact edit. Our benchmark extracts relevant logical rules from a knowledge graph for a given edit. Then, it generates multi-hop questions based on these rules to assess the impact on logical consequences. Our findings indicate that while existing knowledge editing approaches can accurately insert direct assertions into LLMs, they frequently fail to inject entailed knowledge. Specifically, experiments with popular methods like ROME and FT reveal a substantial performance gap, up to 24%, between evaluations on directly edited knowledge and on entailed knowledge. This highlights the critical need for semantics-aware evaluation frameworks in knowledge editing.
Keywords: dice sailproject moteu kouagou zahera ngonga

Kritische Einsprachigkeitsdidaktik als kasuistischer Ansatz für die Lehrkräftebildung - Büttner, Denise (Migrationspädagogische Zweitsprachdidaktik)

Water-assisted proton conductivity and a magnetic study of heterotrinuclear oxalate-bridged compounds: molecular precursors for the Mn2CrO4 spinel - Lozančić, Ana; Burazer, Sanja; Wagner, Tobias; Molčanov, Krešimir; Pajić, Damir; Androš Dubraja, Lidija; Tiemann, Michael; Jurić, Marijana (Journal of Materials Chemistry C)
Novel oxalate-bridged heterotrinuclear complexes [A][Mn2Cr(bpy)2(H2O)2Cl2(C2O4)3] (A = (CH3)2(C2H5)NH+ (1) and (CH3)(C2H5)2NH+ (2); bpy = 2,2′-bipyridine) were synthesized using an aqueous solution of [A]3[Cr(C2O4)3] as a building block in reaction with Mn2+ ions and with the addition of the N-donor ligand bipyridine. The isostructural heterometallic complex salts were characterized by single-crystal and powder X-ray diffraction, infrared and impedance spectroscopy, thermal analysis and magnetization measurements. The trinuclear anion [{Mn(bpy)(H2O)Cl(μ-C2O4)}2Cr(C2O4)]− consists of two [Mn(bpy)(H2O)Cl]+ units bridged by the [Cr(C2O4)3]3− anion, which acts as a bidentate ligand towards each of the manganese atoms. The anions are hydrogen bonded to each other via coordinated chloride anions, water molecules and oxygen oxalate atoms, resulting in two-dimensional (2D) hydrogen bonding layers. Compounds exhibit water-assisted proton conductivity behaviour, which was investigated at different temperatures and relative humidities (RH). At 25 °C, an increase in RH from 60% to 93% resulted in an obvious proton conducting switch from 9.1 × 10−11 to 5.6 × 10−5 S cm−1 for 1 and from 7.4 × 10−10 to 1.8 × 10−6 S cm−1 for 2, corresponding to high on/off ratios of about 106 for 1 and 104 for 2. In situ powder X-ray diffraction (PXRD) analysis showed that unit cell parameters of compounds 1 and 2 slightly increase when exposed to humid conditions. This confirmed that incorporation of water molecules into structures with pores and voids causes the proton conductivity switching phenomenon. Magnetic susceptibility measurements indicate a ferromagnetic interaction between Cr3+ and Mn2+ ions bridged by the bis(bidentate) oxalate group. The prepared compounds 1 and 2 were explored as single-source precursors for the formation of spinel oxide by their thermal treatment. With increasing temperature, the spinel composition changed according to the formula Mn1+xCr2–xO4 (0 ≤ x ≤ 1), where x = 0.7 at 500 °C and x = 1 at 900 °C when tet[MnII]oct[MnIIICrIII]O4 is formed. The (micro)structure, morphology, and optical properties of spinel Mn2CrO4 were characterized by PXRD, scanning electron microscopy and UV-Vis diffuse reflectance spectroscopy. The photocatalytic activity of this oxide in degradation of the methylene blue dye under Vis irradiation without and with the support of hydrogen peroxide was further investigated.

DNA origami adsorption at single-crystalline TiO2 surfaces - Xu, Xiaodan; Gołębiowska, Sandra; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Keller, Adrian (RSC Applied Interfaces)
DNA origami adsorption at single-crystalline TiO 2 surfaces is investigated at different Mg 2+ concentrations. For TiO 2 (001), DNA origami adsorption is stronger at 5 mM than at 10 mM Mg 2+ , whereas the opposite is observed for TiO 2 (110) and TiO 2 (111).

Umkämpfte Semantiken des ‚Europäischen‘ in der Weltanschauungsliteratur der Zwischenkriegszeit - Heise, Tillmann (Forum Interdisziplinäre Begriffsgeschichte)

In Situ Alloying of Ti-6Al-7Nb with Copper Using Laser Powder Bed Fusion - Steinmeier, Paul; Hoyer, Kay-Peter; Lopes Dias, Nelson Filipe; Zielke, Reiner; Tillmann, Wolfgang; Schaper, Mirko (Crystals)
Titanium alloys are widely employed for biomedical implants due to their high strength, biocompatibility, and corrosion resistance, yet their lack of intrinsic antibacterial activity remains a major limitation. Incorporating copper, an antibacterial and β-stabilising element, offers a promising strategy to enhance implant performance. This study investigates Ti-6Al-7Nb modified with 1–9 wt.% Cu via in situ alloying during metal-based laser powder bed fusion (PBF-LB/M), with the aim of assessing processability, microstructural evolution, and mechanical properties. Highly dense samples (>99.9%) were produced across all Cu levels, though chemical homogeneity strongly depended on processing parameters. Increasing Cu content promoted β-phase stabilisation, Ti2Cu precipitation, and pronounced grain refinement. Hardness and yield strength increased nearly linearly with Cu addition, while ductility decreased sharply at ≥5 wt.% Cu due to intermetallic formation, hot cracking, and brittle fracture. These results illustrate both the opportunities and constraints of rapid alloy screening via PBF-LB/M. Overall, moderate Cu additions of 1–3 wt.% provide the most favourable balance between mechanical performance, manufacturability, and potential antibacterial functionality. These findings provide a clear guideline for the design of Cu-functionalised titanium implants and demonstrate the efficiency of in situ alloy screening for accelerated materials development.
Keywords: Biomaterial; In Situ Alloying; Titanium; Additive Manufacturing

INNOVADE Interdisciplinary Knowledge Base on Digital Democracy - D2.1 - Fuchs, Christian; Friesch, Kevin; Museba, Joel
This report outlines foundations of digital democracy and digital democracy research. It is structured into eight chapters: Chapter 1: Introduction Chapter 2: What is Digital Democracy? Chapter 3: Online Participation Chapter 4: Open Governance Chapter 5: Digital Activism Chapter 6: e-Voting Chapter 7: Global Trends that Influence Digital Democracy Chapter 8: Foreign Interferences in Democracy

Counting Components of Hurwitz Spaces - Seguin, Beranger Fabrice (Israel Journal of Mathematics)
For a finite group $G$, we describe the asymptotic growth of the number of connected components of Hurwitz spaces of marked $G$-covers (of both the affine and projective lines) whose monodromy classes are constrained in a certain way, as the number of branch points grows to infinity. More precisely, we compute both the exponent and (in many cases) the coefficient of the leading monomial in the count of components containing covers whose monodromy group is a given subgroup of $G$. By the work of Ellenberg, Tran, Venkatesh and Westerland, this asymptotic behavior is related to the distribution of field extensions of~$\mathbb{F}_q(T)$ with Galois group $G$.

Realization functors in algebraic triangulated categories - Letz, Janina Carmen; Sauter, Julia (Abh. Math. Semin. Univ. Hambg.)